Smart Wallets, Stress-Free Lives: Determinants of Financial Wellness in Kathmandu - Mahato, Surendra; Darji, Puja (KIC International Journal of Social Science and Management, 2024)
As the financial world becomes more sophisticated, personal financial well-being (FWB) is a measure of strength and stability. This study examines how FWB affects Kathmandu, Nepal, a South Asian metropolis that is urbanizing and blending modern and ancient banking practices. The study examines how financial knowledge, behavior, attitude, stress, and satisfaction affect FWB. Quantitative research using structured questionnaires was employed to collect primary data from a wide spectrum of Kathmandu residents. We examined variable relationships using structural equation modeling (SEM). Results demonstrate that financial knowledge, attitude, stress, and contentment strongly affect FWB. Financial activity doesn’t directly affect much. This contradicts the idea that good financial practices are enough to promote health. The results demonstrate the importance of a complete financial education program that increases understanding, promotes positivity, and addresses emotional and mental aspects of financial life. This study contributed to the scholarly discussion regarding FWB in developing urban areas and provides policymakers, instructors, and financial service providers in Nepal and elsewhere with relevant information. As the financial world gets more complicated, personal financial well-being (FWB) is a key indicator of stability and resilience. This study examines how FWB affects Kathmandu, Nepal, a South Asian metropolis that is urbanizing and blending modern and ancient banking practices. The study examines how financial knowledge, behavior, attitude, stress, and satisfaction affect FWB. Quantitative research using structured questionnaires was employed to collect primary data from a wide spectrum of Kathmandu residents. We examined variable relationships using structural equation modeling (SEM). Results demonstrate that financial knowledge, attitude, stress, and contentment strongly affect FWB. Financial activity doesn’t directly affect much. This contradicts the idea that good financial practices are enough to promote health. The results demonstrate the importance of a complete financial education program that increases understanding, promotes positivity, and addresses emotional and mental aspects of financial life. This research contributes to the scholarly discussion on FWB in developing cities and informs policymakers, instructors, and financial service providers in Nepal and beyond.